Safe staple less laparoscopic splenectomy; use of Hem-o-Lok to control the splenic hilum - Sherif Mohammed Farahat; Akram Elbatarny; Khalid Mohamed. Elshimy; Sherif Medhat; Khalid Ahmed Ismail; Mohamed Ahmed Arafa (Journal of the Pakistan Medical Association, 2023)
Objective: To evaluate Hem-o-Lok polymer clips’ feasibility, safety and cost-effectiveness in controlling the splenic pedicle during paediatric laparoscopic splenectomy. Method: The prospective study was conducted from May 2019 to December 2021 at Kafrelsheikh University Hospital, Egypt, and comprised children of either gender aged <18 years who had benign haematological diseases and were indicated for laparoscopic splenectomy. During the procedure, Hem-o-Lok clips were used for controlling the splenic pedicle. Patients were encouraged to ambulate the same day, and the drain was removed 24hours postoperatively. The cases were followed up for three months postoperatively. Results: Of the 23 subjects, 11(47.8%) were boys and 12(52.2%) were girls. The overall mean age was 8.74±3.44 years (range: 4-15 years). There were 6(26%) cases of spherocytosis, 1(4.3%) immune thrombocytopenic purpura and 16(69.6%) with thalassemia major. The mean operative time was 93.43±29.87 minutes (range: 65-180 minutes). There was no conversion to open splenectomy and no mortality. There were 2(8.7%) cases of minor and 1(4.3%) of major intraoperative bleeding. All the 3(100%) cases were controlled laparoscopically. No postoperative bleeding occurred and no cases required postoperative blood transfusion. Conclusion: Controlling both the splenic artery and vein using Hem-o-Lok clips was found to be feasible, safe and cost-effective. Keywords: Purpura, Thrombocytopenic, Idiopathic, Spleen, Splenic artery, Thalassemia, Laparoscopy, Polymers.